Welding Skills Improvement Training in Lanne Village, Pangkep Regency - Amme, Rudi; Salam, Nasaruddin; Renreng, Ilyas; Tarakka, Rustan; Arma, Lukmanul Hakim; Arsyad, Hairul; Mochtar, Andi Amijoyo; Hayat, Azwar; Sakka, Asriadi (Faculty of Engineering UNHAS, 2025)
The welding method combines two or more pieces of metal by melting the material to be joined. The joining of two or more base metals through melting or without melting the joint area is known as welding technology. Karang Taruna Desa Lanne is a village government program for youth empowerment. Currently, the youth organization has a program that still needs to be improved to increase the productivity of youth organization members. Therefore, the training program to improve welding skills initiated by the Department of Mechanical Engineering, Faculty of Engineering, Hasanuddin University, is expected to positively impact partners. The activity was carried out by providing training material followed by welding practice activities to determine the ability of participants to apply the material provided previously. In addition, the pre-test and post-test questionnaires were given to the participants before and after the training to determine the program's success rate. Based on the quantitative analysis of measurements before training, it was found that 85% did not understand and 15% did not understand how to prepare for welding. After the training, it was found that 65% of the participants understood, 25% understood, and 10% understood very well when preparing for welding. This indicates that the activities carried out have a positive impact on partners.